Porosity Effect of Sintered Steel on the Frictional Performance of Conformal and Nonconformal Lubricated Contacts. Issue 6 (2nd November 2019) - Boidi, G.; Tertuliano, I. S.; Lima, L. G. B. S.; Profito, F. J.; Machado, I. F.
Abstract: The effect of surface topography on lubricated systems plays a crucial role in terms of friction performance, because surface micro-irregularities can improve the load-carrying capacity of mechanical parts in lubricated conformal and nonconformal contacts. Sintered materials, which can be applied to manufacturing several mechanical components such as gears, axial thrust bearings, and disc brake pads, are interesting candidates, because they present pores that could be somewhat compared to microcavities produced by surface texturing techniques. This work aims at studying the influence of surface pores originated from the sintering process on the frictional performance of lubricated contacts under different lubrication regimes and slide-to-roll ratios (SRR). The research contributes to understanding how random micro-irregularities could change lubrication conditions and promote effects similar to those of more expensive and precise surface features produced by texturing techniques. The experimental results showed that a decrease in porosity led to a reduction in the coefficient of friction. Furthermore, less porous samples promoted friction reduction compared to nonporous materials due to the probable additional load support caused by small-scale surface pores. Therefore, in addition to the traditional appeal of the use of sintered materials to reduce production costs, the present contribution reveals that this type of material could also be used to reduce friction in contacting mechanical components operating under certain tribological conditions.